Structural basis for the broad and potent cross-reactivity of an N501Y-centric antibody against sarbecoviruses - Jeong, Bo-Seong; Jeon, Joon Young; Lai, Chih-Jen; Yun, Hye-Yeoung; Jung, Jae U.; Oh, Byung-Ha (Frontiers in Immunology, 2022)
More than 80% of SARS-CoV-2 variants, including Alpha and Omicron, contain an N501Y mutation in the receptor-binding domain (RBD) of the spike protein. The N501Y change is an adaptive mutation enabling tighter interaction with the human ACE2 receptor. We have developed a broadly neutralizing antibody (nAb), D27LEY, whose binding affinity was intentionally optimized for Y501. This N501Y-centric antibody not only interacts with the Y501-containing RBDs of SARS-CoV-2 variants, including Omicron, with pico- or subnanomolar binding affinity, but also binds tightly to the RBDs with a different amino acid at residue 501. The crystal structure of the Fab fragment of D27LEY bound to the RBD of the Alpha variant reveals that the Y501-containing loop adopts a ribbon-like topology and serves as a small but major epitope in which Y501 is a part of extensive intermolecular interactions. A hydrophobic cleft on the most conserved surface of the RBD core serves as another major binding epitope. These data explain the broad and potent cross-reactivity of this N501Y-centric antibody, and suggest that a vaccine antigenic component composed of the RBD core and a part of RBM containing tyrosine at residue 501 might elicit broad and potent humoral responses across sarbecoviruses.